La representación de la mujer en la música de Bad Bunny: Análisis de la percepción social - Rodriguez Gamboa, Joseline Betsy (2025)
This research work analyzes the perception of women in the songs of urban artist Bad Bunny, exploring the social perception generated by his lyrics and video clips in the public of the city of Babahoyo. A descriptive and correlational research approach is used through a mixed method where quantitative and qualitative techniques are employed. The study addresses the relationship between the messages of their songs and their attitudes about gender roles and stereotypes, identifying both elements of female empowerment and cases of perpetuation of stereotypes. The research proposes that urban music, especially Bad Bunny's content, has a significant impact on the construction of social imaginaries related to women, which allows us to understand how gender roles are integrated, challenged or reinforced in a globalized context, providing a basis for promoting more equitable and respectful representations.